Now or Later? Stress-Induced Increase and Decrease in Choice Impulsivity Are Both Associated with Elevated Affective and Endocrine Responses - Lisa Simon; Talita Jiryis; Roee Admon (Brain Sciences, 2021)
Exposure to acute stress elicit physiological and psychological responses that can impact decision-making, often expressed as an increased tendency to act in an impulsive manner following stress. Delay discounting (DD) task has emerged as a reliable measure of impulsive behavior in the form of choice impulsivity (CI). Interestingly, studies that examined the effect of acute stress on DD performance reported mixed results. To address this, we conducted a within-subject examination of the impact of acute stress on CI, focusing on individual differences in response patterns. One hundred and fifty healthy female participants completed the DD task twice, before and after undergoing an acute laboratory stress induction procedure. Saliva samples and self-report mood and affect measures were collected at four time points throughout the session. Fifty-nine matched healthy control participants completed only the DD task twice, with no stress in between. Results indicate that the acute stress procedure elicited the expected effects of increased cortisol release and increased negative mood and affect, at the group level. With respect to DD, stress indeed increased CI at the group level, yet participants differed in the magnitude and direction of this effect. Interestingly, regression analysis revealed quadratic relations between stress-induced changes in CI and cortisol release. Indeed, dividing the sample into three sub-groups based on the impact of stress on CI revealed that, compared to participants that exhibited no substantial change in their CI following stress, participants that exhibited either stress-induced increase or decrease in their CI also exhibited more stress-induced cortisol release, as well as more negative affect. Taken together, these findings suggest that elevated physiological and psychological responses to stress are associated with either increased or decreased choice impulsivity, thus depicting quadratic relations between stress and impulsivity.